Dealing with highly fuzzy landscapes: how to assess High Nature Value Farmland in Mediterranean silvo-pastoral systems - Pinto-Correia, T. (2015)
The 9th IALE world congress a joint meeting between the International Association of Landscape Ecology World Congress (WC) and the US chapter of IALE (US-IALE). The Meeting Theme was Crossing Scales, Crossing Borders: Global Approaches to Complex Challenges. Teresa Pinto Correia was co-organizer of the symposium S45 “Shaping landscape ecology approaches in different regional contexts” and presenter of “Dealing with highly fuzzy landscapes: how to assess High Nature Value Farmland in Mediterranean silvo-pastoral systems”- The MONTADO: Mediterranean silvo-pastoral system with extensive land use, several layers, functional complexity, high spatial fuzziness, the effect of farm management shift in High Nature Value farmland.